2009
DOI: 10.1117/1.3088100
|View full text |Cite
|
Sign up to set email alerts
|

In vivo time-resolved spectroscopy of the human bronchial early cancer autofluorescence

Abstract: Time-resolved measurements of tissue autofluorescence (AF) excited at 405 nm were carried out with an optical-fiber-based spectrometer in the bronchi of 11 patients. The objectives consisted of assessing the lifetime as a new tumor/normal (T/N) tissue contrast parameter and trying to explain the origin of the contrasts observed when using AF-based cancer detection imaging systems. No significant change in the AF lifetimes was found. AF bronchoscopy performed in parallel with an imaging device revealed both int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The reported sensitivity of many of these devices for detecting specific diseases stages is high, but their specificity remains limited. 2,42,93 This is due to a number of factors emerging from the difficulty to conduct absolute emission intensity measurements in vivo . The fluorescence intensity measurements are affected by changes in light excitation-collection geometries due to tissue movement, presence and change in concentration of endogenous absorbers (e.g.…”
Section: Fluorescence In Tissue Characterization and Diagnosismentioning
confidence: 99%
“…The reported sensitivity of many of these devices for detecting specific diseases stages is high, but their specificity remains limited. 2,42,93 This is due to a number of factors emerging from the difficulty to conduct absolute emission intensity measurements in vivo . The fluorescence intensity measurements are affected by changes in light excitation-collection geometries due to tissue movement, presence and change in concentration of endogenous absorbers (e.g.…”
Section: Fluorescence In Tissue Characterization and Diagnosismentioning
confidence: 99%
“…which usually associates with changes of endogenous fluorophores and can be monitored by fluorescence. Recent studies have revealed the potential of autofluorescence imaging [9], [10], [11] and spectroscopy [12], [13] as diagnostic methods, including oral [8] cervical [14], [15] and breast [16] cancers. Since the irregular tissue surface or endogenous absorbers in tissues, the quantitatively measurement of fluorescence intensity remains a challenge [17].…”
Section: Introductionmentioning
confidence: 99%
“…AF from the elastin network in the submucosa provided the major fluorescence signal following 405 nm excitation and was proposed to be used to distinguish tumoral tissue in the human bronchial early cancer (Uehlinger et al 2009); however, these authors did not identify changes in the fluorescence lifetimes in the diseased tissue.…”
Section: Elastinmentioning
confidence: 98%